Novel antimicrobial zein film for controlled release of lauroyl arginate (LAE). (December 2016) - Kashiri, Mahboobeh; Cerisuelo, Josep P.; Domínguez, Irene; López-Carballo, Gracia; Hernández-Muñoz, Pilar; Gavara, Rafael
Abstract: Novel antimicrobial biopolymer films based on the incorporation of ethyl-N α -dodecanoyl-l -arginate hydrochloride (LAE) in zein matrices were manufactured and characterized as materials for LAE controlled released applications such as active food packaging. Characterization of the films' functional properties revealed that incorporation of LAE (5 and 10%) in the biopolymer matrix did not cause substantial changes in morphological, optical, thermal, mechanical and barrier properties. As the mechanism of action of these films is mainly based on release of the antimicrobial, this process was characterized when the active biofilms were exposed to three food simulants (water, 3% acetic acid, and 10% alcohol) at three temperatures (4, 23, and 37 °C). The data obtained revealed that, with the exception of exposure to water at 4 °C which achieved a release of more than 80% of the LAE incorporated, the agent was almost completely extracted in all conditions. Release of LAE was faster at higher temperatures, and the diffusion coefficient values varied according to the Arrhenius law, and increased with temperature. Antibacterial activity of films was assayed against Listeria monocytogenes and Escherichia coli . Zein films with 5% LAE produced 2.02 and 3.07 log reduction against L. monocytogenes and E. coli, respectively, after 5 days of storage at 4 °C. Greater antibacterial activity was observed with films containing 10% LAE (5 log reduction) at 37 °C. This work highlighted that LAE incorporation in a packaging film constructed with renewable polymer materials offers an interesting and efficient hurdle for control of bacterial contamination in foods. Graphical abstract: Highlights: LAE successfully incorporated into water-resistant homogeneous zein films. LAE addition up to 10% do not alter substantially zein film functional properties. LAE is released into aqueous food simulants in a Fickian controlled process. LAE release from films efficiently inhibit the growth of Listeria monocytogenes and Escherichia coli .